Editorial Board and Guidelines for the Authors - TAWARIKH, Editor Journal (TAWARIKH, 2015)
TAWARIKH will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the history education and historical studies, and its various aspects. Analysis will be practical and rigorous in nature.Bandung, Indonesia: October 28, 2015.